Social movements and collective behavior: an integration of meta-analysis and systematic review of social psychology studies - da Costa, Silvia; Páez, Dario; Martí-González, Mariacarla; Díaz, Virginia; Bouchat, Pierre (Frontiers in Psychology, 2023)
This paper seeks to review the patterns of CB and corroborate the psychosocial factors that explain participation in CB and SM, as well as the long-term psychological effects of participating in them. A systematic search was carried out in the databases for articles dated between 1969 and 2022. Of 494 initial records, 16 meta-analyses and systematic reviews were analyzed. The evidence reviewed shows that participation in collective gatherings and CB are common. A cross-cultural survey suggests that collective gatherings are mostly of a leisure type, to a lesser extent religious and sporting, and to an even lesser extent, demonstrations and large religious rites. World Value surveys found that one to three persons out of 10 participate in protests or CB related to SM and 4 out of 10 movements achieved some kind of success. Studies challenged that CBs were characterized by unanimity of beliefs, identification and behaviour, generalized excitement as well as mass panic and riot after catastrophes. Only two out of ten CB are violent. Participation in CB and SM was associated with: a) intergroup conflict and realistic threat, b) positive attitudes, expectations or agreement with goals or collective motive, c) cognitive fraternal relative deprivation, d) collective efficacy, e) collective identity, f) emotions and affective relative deprivation, g) moral conviction and threat to moral, and h) disagreement with system justification belief. Participation in successful CB and SM provokes positive changes in emotions, social identity and social relationships, values and beliefs, and empowerment – as well as negative effects such as depression, stress, burnout and disempowerment related to the failures of SM. Participation in successful CB and SM provokes positive changes in emotions, social identity and social relationships, values and beliefs, and empowerment – as well as negative effects such as depression, stress, burnout and disempowerment related to the failures of SM. Studies confirm the importance of explanatory factors for SM, with data from various cultural regions. There is a lack of systematic studies of CB as well as meta-analyses and more culturally diverse studies of the effects of participation in them.